The efficacy of the ultraviolet C pathogen inactivation system in the reduction of Babesia divergens in pooled buffy coat platelets. Issue 9 (25th March 2014) - Castro, Emma; González, Luis Miguel; Rubio, Jose Miguel; Ramiro, Raquel; Gironés, Núria; Montero, Estrella
<x xml:space="preserve">Abstract</x> Background Babesia spp. is an intraerythrocytic parasite that causes human babesiosis and its transmission by transfusion has been extensively demonstrated. The aim of this study was to ascertain the efficacy of an ultraviolet C (UVC)‐based pathogen inactivation system in the reduction of Babesia divergens–infected platelet (PLT) concentrates and to determine the parasite's ability to survive in PLT concentrates stored under blood bank conditions. Study Design and Methods This study was conducted using in vitro cultures of B. divergens. The detection limit of the culture assay was established and, subsequently, 15 buffy coat–derived PLT concentrates (BC‐PCs) were inoculated with 107B. divergens–infected red blood cells. Infected BC‐PCs were irradiated with 0.2 J/cm2 UVC light using the THERAFLEX UV‐Platelets method (Macopharma). Viability and parasite growth were evaluated before and after inactivation. Culture growth kinetics were monitored by DNA incorporation of [3H]thymidine. The ability of B. divergens to survive in PLT concentrates was also analyzed. Results The limit of detection in cultures was established at 0.1 × 10−6% parasites. The THERAFLEX UV‐Platelets system inactivated B. divergens to below the limit of detection in 12 of 15 BC‐PCs (log reduction, >6.0) and to the limit of detection (log reduction, 5.0) in three of 15. It was also demonstrated that B. divergens remains viable in BC‐PCs stored up to 7 days. Conclusion Since B. divergens can survive in PLT concentrates and given the performance of UVC, this system could be considered as an alternative to prevent B. divergens and other Babesia species from being transmitted through PLT transfusions.